1996
DOI: 10.1002/anie.199610501
|View full text |Cite
|
Sign up to set email alerts
|

Free‐Radical Carbonylations: Then and Now

Abstract: Although known since the 1950s, free‐radical carbonylation has not received much attention until only recently. In the last few years the application of modern free‐radical techniques has revealed the high synthetic potential of this reaction as a tool for introducing CO into organic molecules. Clearly now is the time for a renaissance of this chemistry. Under standard conditions (tributyltin hydride/CO) primary, secondary, as well as tertiary alkyl bromides and iodides can be efficiently converted into the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
98
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 291 publications
(101 citation statements)
references
References 163 publications
1
98
0
2
Order By: Relevance
“…[50] Corresponding carbonylations of aliphatic hydrocarbons with carbon monoxide under nonoxidizing conditions are of particular industrial interest since such processes might be able to compete with hydroformylation. Since the early work of Tanaka et al, radical reactions, [51] which in addition to the transition metal catalysis require photochemical activation, have been favored for this. Whereas Tanaka et al…”
Section: à H Activation Without Cyclometalationmentioning
confidence: 99%
“…[50] Corresponding carbonylations of aliphatic hydrocarbons with carbon monoxide under nonoxidizing conditions are of particular industrial interest since such processes might be able to compete with hydroformylation. Since the early work of Tanaka et al, radical reactions, [51] which in addition to the transition metal catalysis require photochemical activation, have been favored for this. Whereas Tanaka et al…”
Section: à H Activation Without Cyclometalationmentioning
confidence: 99%
“…[3] We recently reported a related transformation that can be achieved by using tetrabutylammonium cyanoborohydride as an alternative for toxic tin hydride.…”
mentioning
confidence: 99%
“…[1] Many cases of previously reported radical carbonylation utilize highly toxic organotin reagents as mediators. [2,3] In connection with our interest on tin-free radical reactions, [4] we have reported that alkyl allyl sulfone precursors are very effective for radical carbon-carbon bond formation under tin-free conditions.…”
mentioning
confidence: 99%
“…[5] Furthermore, we also reported the synthesis of thiol esters and acyl cyanides based on tinfree radical carbonylations using alkyl allyl sulfone precursors [Eq. (1)]. [6,7] In our continued efforts to develop tin-free radical carbonylation reactions, we have studied the radical reactions of sulfonyl oxime ether 2 [8] with alkyl allyl sulfone precursors under CO pressure to achieve consecutive radical acylations in an indirect manner under tin-free conditions [Eq.…”
mentioning
confidence: 99%